2021
DOI: 10.3389/fsurg.2021.633196
|View full text |Cite
|
Sign up to set email alerts
|

Multiparametric MRI may Help to Identify Patients With Prostate Cancer in a Contemporary Cohort of Patients With Clinical Bladder Outlet Obstruction Scheduled for Holmium Laser Enucleation of the Prostate (HoLEP)

Abstract: Objective: To investigate the value of standard [digital rectal examination (DRE), PSA] and advanced (mpMRI, prostate biopsy) clinical evaluation for prostate cancer (PCa) detection in contemporary patients with clinical bladder outlet obstruction (BOO) scheduled for Holmium laser enucleation of the prostate (HoLEP).Material and Methods: We retrospectively analyzed 397 patients, who were referred to our tertiary care laser center for HoLEP due to BOO between 11/2017 and 07/2020. Of those, 83 (20.7%) underwent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…One compared HoLEP with both OP and TURP (Capogrosso et al, 2018). Regarding the quality of the studies, 52.6% of our studies were adequate/fair (Capogrosso et al, 2018;He et al, 2020;Herlemann et al, 2017;Kim et al, 2014;Martos et al, 2021;Nunez et al, 2011;Otsubo et al, 2015;Rivera et al, 2014;Rosenhammer et al, 2018b;Tominaga et al, 2019), 36.8% good Elkoushy et al, 2015;Ohwaki et al, 2017;Porreca et al, 2019Porreca et al, , 2020Rosenhammer et al, 2018a;Wenzel et al, 2021) and 10.6% strong quality (Bhojani et al, 2015;Magistro et al, 2020).…”
Section: Re Sultsmentioning
confidence: 72%
See 2 more Smart Citations
“…One compared HoLEP with both OP and TURP (Capogrosso et al, 2018). Regarding the quality of the studies, 52.6% of our studies were adequate/fair (Capogrosso et al, 2018;He et al, 2020;Herlemann et al, 2017;Kim et al, 2014;Martos et al, 2021;Nunez et al, 2011;Otsubo et al, 2015;Rivera et al, 2014;Rosenhammer et al, 2018b;Tominaga et al, 2019), 36.8% good Elkoushy et al, 2015;Ohwaki et al, 2017;Porreca et al, 2019Porreca et al, , 2020Rosenhammer et al, 2018a;Wenzel et al, 2021) and 10.6% strong quality (Bhojani et al, 2015;Magistro et al, 2020).…”
Section: Re Sultsmentioning
confidence: 72%
“…In their study investigating the value of mpMRI and prostate biopsy in diagnosing PCa in patients scheduled for HoLEP, Wenzel et al reported iPCa in 9 (11.8%) patients with no previous PCa diagnosis who had undergone HoLEP (Wenzel et al, 2021). In their study, they reported that Prostate Imaging-Reporting and Data System 4 and five lesions detected via mpMRI before HoLEP function as independent predictors of PCa (OR: 9.91, p = 0.04).…”
Section: Role Of Imaging Modalities In Detecting Ipca After Holepmentioning
confidence: 97%
See 1 more Smart Citation
“…PCa can also be incidentally diagnosed after transurethral resection 13 or holmium laser enucleation of prostate for BPH. It might be also diagnosed by imaging technick for BPH, 14 other diseases 15 or imaging of metastatic disease in low PSA prostate cancer 4–6 …”
Section: Discussionmentioning
confidence: 99%
“…Considering the role of MRI to detect to predict IPCa after HoLEP, Wenzel et al . demonstrated that Prostate Imaging‐Reporting and Data System (PI‐RADS) 4 and 5 lesions detected by multiparametric MRI (mpMRI) prior HoLEP could be independent predictors of IPCa (OR 9.91, P = 0.04) 4 . This finding suggested that clinicians can consider mpMRI before HoLEP as a worthwhile option to detect IPCa.…”
mentioning
confidence: 96%